The Southern Energy Corridor: Competition and Cooperation for Natural Gas Transportation in the Black Sea and Caspian Region - Hardy, Liam P (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of International Business at the Fletcher School of Law and Diplomacy. The Southern Energy Corridor emerged as an idea describing the network of oil and gas pipelines bringing resources from the Caucasus through Turkey to Eastern Europe. It arose as a way for Europe to diversify its energy dependence on Russia, which supplies roughly 40% of the market. The thesis evaluates the various projects for transporting natural gas in the Caucasus and Southeast Europe and the strategic nature of each project. It also addresses the key risk variables for the projects that make up the Southern Energy Corridor and provides recommendations for key policymakers and private sector stakeholders.